Synthesis of a Flat-bottom Follower Cam-linkage Mechanism with Swing Variable Pivot - Guanglu Yang; Tao Zhang; Suijun Liu; Liangwen Wang; Zhongfu Lu; Xuede Chen; Tuanhui Wang (Jixie chuandong)
A flat-bottom follower cam-linkage mechanism with a swing follower with variable pivot has been studied which is used in cleaning equipment of tobacco machinery. In this mechanism，the pivot of the swing follower is installed on a slider with an adjustable track direction，the follower performs a complex planar motion，and the motion range of the output angle can be adjusted according to the output requirements. In order to synthesize this mechanism，firstly，the relevant model is established. Secondly，the inverse method and the envelope theory are employed to derive the solving model of the cam contour coordinates. Finally，the corresponding follower motion law is selected，the corresponding cam contour coordinates are calculated，and the entire cam contour curve is obtained using interpolation. The motion cam of an example mechanism is designed by using this processes and verified through motion simulations. The study work solves the equipment needs and enriches the design theory of cam-linkage mechanisms.